2014
DOI: 10.1016/j.bbadis.2014.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acids are novel nutrient factors to regulate mTORC1 lysosomal localization and apoptosis in podocytes

Abstract: Podocyte apoptosis is a potent mechanism of proteinuria in diabetic nephropathy. More detailed mechanistic insight into podocyte apoptosis is needed to better understand the pathogenesis of diabetic nephropathy. An elevated level of serum free fatty acid (FFA), as well as hyperglycemia, is a clinical characteristic in diabetes, although its causal role in podocyte apoptosis remains unclear. This study examined the effect of three types of FFAs, saturated, monounsaturated and polyunsaturated FFAs, on podocyte a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
90
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(94 citation statements)
references
References 57 publications
4
90
0
Order By: Relevance
“…(1,5,11,12), may also have a role in modulating the postprandial muscle protein synthetic response in healthy adults. For example, as part of its whole-food matrix, the egg yolk contains various nonprotein food components that may have anabolic properties, such microRNAs (33), vitamins (34,35), minerals (36), and lipids [e.g., phosphatidic acid (37), palmitic acid (38), and DHA (39)] by modifying pathways related to transcriptional or protein translational control. However, more work is required to systematically assess the role of such food components on modulating postprandial muscle protein synthesis rates in vivo in humans.…”
Section: Figurementioning
confidence: 99%
“…(1,5,11,12), may also have a role in modulating the postprandial muscle protein synthetic response in healthy adults. For example, as part of its whole-food matrix, the egg yolk contains various nonprotein food components that may have anabolic properties, such microRNAs (33), vitamins (34,35), minerals (36), and lipids [e.g., phosphatidic acid (37), palmitic acid (38), and DHA (39)] by modifying pathways related to transcriptional or protein translational control. However, more work is required to systematically assess the role of such food components on modulating postprandial muscle protein synthesis rates in vivo in humans.…”
Section: Figurementioning
confidence: 99%
“…The mouse podocyte cell line was cultured as previously described (27,28). Differentiated cells were stimulated with high glucose (500 mg/dL), fatty acids (palmitate and oleate, 150 mmol/L each), tumor necrosis factor-a (TNFa, 10 ng/mL), or serum for 24 h. Sera were collected from the indicated rodent models and patients.…”
Section: Cell Culturementioning
confidence: 99%
“…Uzu and colleagues found that saturated free fatty acids such as palmitate activated mTORC1, suppressed autophagy and induced ER stress-dependent apoptosis in podocytes. Interestingly, unsaturated free fatty acids including oleate showed the opposite effects and ameliorated palmitate-induced ER stress and apoptosis [24]. Dong et al [25] reported that mTORC1 was rapidly activated during ER stress and involved in ER stressinduced apoptosis of renal proximal tubular cells, possibly by suppressing autophagy.…”
Section: Autophagy Protects Renal Cells From Endoplasmic Reticulum Stmentioning
confidence: 99%